1986
DOI: 10.3109/00365528609034629
|View full text |Cite
|
Sign up to set email alerts
|

The Acid Perfusion Test in Gastroesophageal Reflux Disease

Abstract: An acid perfusion test, isotope scanning, endoscopy, and esophageal biopsy were performed in 101 patients with symptoms strongly suggestive of gastroesophageal reflux (GER) disease. A positive acid perfusion test within 30 min (APT) and within 5 min (TAPT) was found in 70.2% and 37.6% of the patients, respectively. A positive APT was found significantly more often in patients with than without endoscopic esophagitis, whereas a positive TAPT was found significantly more often in patients with severe symptoms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Therefore, our data may indirectly suggest less visceral perception in NERD patients by showing diminished sympathetic modulation in these patients. This notion is in line with a previous study by Kaul et al in which it was shown that NERD patients are less sensitive in comparison with patients with ERD [30].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, our data may indirectly suggest less visceral perception in NERD patients by showing diminished sympathetic modulation in these patients. This notion is in line with a previous study by Kaul et al in which it was shown that NERD patients are less sensitive in comparison with patients with ERD [30].…”
Section: Discussionsupporting
confidence: 88%
“…Although the basic principal of the test remained similar, many investigators have tried different acid perfusion rates, concentrations, and durations in the hope of increasing the sensitivity of the test. [27][28][29][30][31][32][33][34] Furthermore, some have even suggested the addition of bile salts to the acid solution. 35 Many attempts were made to change the test from a qualitative to a quantitative tool.…”
Section: Acid Perfusion Test (Bernstein Test)mentioning
confidence: 99%
“…Although not widely appreciated, esophageal acid perfusion can elicit heartburn in a majority of healthy volunteers without a history of heartburn [40,41]. Heartburn evoked in volunteers, however, differs from that elicited in patients with esophagitis.…”
Section: Esophagosalivary Reflexmentioning
confidence: 99%
“…Most patients with reflux esophagitis experience reproduction of their heartburn upon perfusion of the esophagus with acid [39][40][41]. Although not widely appreciated, esophageal acid perfusion can elicit heartburn in a majority of healthy volunteers without a history of heartburn [40,41].…”
Section: Esophagosalivary Reflexmentioning
confidence: 99%